Proses Produksi Acara Keislaman Program Cahaya Qolbu TVRI Jawa Barat - Dinata, Resiana; Muhlis, Atjep; Rustandi, Ridwan (Tabligh: Jurnal Komunikasi dan Penyiaran Islam, 2023)
The main purpose of this research is to describe the technical stages of pre-production, production, and post-production in the program "Cahaya Qolbu" on TVRI West Java. The research uses a constructivist paradigm, field research method, descriptive approach with observation, interview, and documentation techniques for data collection. the theory used is the theory of mass media management and the standard operating procedure (SOP) theory. The results show that the pre-production process includes planning the theme based on trending issues and in accordance with the Islamic event calendar, selecting the Da'i and the dynamics of the Majlis Taklim. The production process includes executing shooting exploration through taping and live streaming at the same time and camera angle techniques. The post-production stage includes direct editing system as well as re-editing and periodic evaluation methods to review the production results.